Adverse Fetal and Neonatal Outcome and an Abnormal Vertebral Pattern: A Systematic Review. Issue 12 (December 2016) - Schut, Pauline Christine; Cohen-Overbeek, Titia E.; Galis, Frietson; Ten Broek, Clara M. A.; Steegers, Eric A.; Eggink, Alex J.
Abstract : Importance: The human vertebral column has a stable number of vertebrae and ribs, which is presumably the result of evolutionary selection. An association between an abnormal vertebral pattern, especially in the cervical region, and congenital anomalies or adverse fetal outcome has been reported. Objective: The aim of this study was to review the current literature concerning an abnormal vertebral pattern and prevalence of cervical ribs in healthy subjects and in subjects with adverse outcome. Evidence Acquisition: Scientific databases were searched systematically. Studies assessing the number of vertebrae and/or ribs were included, and data concerning anomalies and outcome were extracted. Results: Thirty-nine studies including 75, 018 healthy subjects and 6130 subjects with structural or chromosomal anomalies or adverse outcome were selected. The majority of these studies focused on the prevalence of cervical ribs. The prevalence of cervical ribs was considerably higher in fetuses with adverse outcome, including aneuploidies, compared with healthy individuals in the vast majority of studies. Studies suggest an association between cervical ribs and other structural anomalies. Conclusions: These results demonstrate that detailed assessment of the fetal vertebral column, especially of the cervicothoracic region, could provide valuable information regarding fetal and neonatal prognosis. Based on the available evidence, the application of 3-dimensional (3D) ultrasound to assess the vertebral column and ribs, in particular the cervical region, warrants further research. Relevance: Prenatal assessment of the ribs and vertebral pattern by 3D ultrasound, which is currently not routinely performed, might be useful in the assessment of the fetus, because this can predict fetal and neonatal outcome in some cases. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to be aware of the possible relation between a disturbed pattern of the vertebral column and adverse fetal outcome; discuss why changes in the pattern of the vertebral column, especially at the cervical level, should be more deleterious than those at the caudal part of the vertebral column; determine whether an abnormal vertebral pattern is more common in fetuses and neonates with adverse outcome than in healthy subjects; and have insight into the usefulness of detailed assessment of the fetal vertebral column by 3D ultrasound.